Irregular water supply, household usage and dengue: a bio-social study in the Brazilian Northeast Abastecimento irregular de água, seu uso domiciliar e dengue: uma pesquisa biossocial no Nordeste do Brasil - Andrea Caprara; José Wellington de Oliveira Lima; Alice Correia Pequeno Marinho; Paola Gondim Calvasina; Lucyla Paes Landim; Johannes Sommerfeld (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
Despite increased vector control efforts, dengue fever remains endemic in Fortaleza, Northeast Brazil, where sporadic epidemic outbreaks have occurred since 1986. Multiple factors affect vector ecology such as social policy, migration, urbanization, city water supply, garbage disposal and housing conditions, as well as community level understanding of the disease and related practices. This descriptive study used a multi-disciplinary approach that bridged anthropology and entomology. A multiple case study design was adopted to include research in six study areas, defined as blocks. The water supply is irregular in households from both under-privileged and privileged areas, however, clear differences exist. In the more privileged blocks, several homes are not connected to the public water system, but have a well and pump system and therefore irregularity of supply does not affect them. In households from under-privileged blocks, where the water supply is irregular, the frequent use of water containers such as water tanks, cisterns, barrels and pots, creates environmental conditions with a greater number of breeding areas. In under-privileged homes, there are more possible breeding areas and environmental conditions that may improve the chances of Aedes aegypti survival. Apesar do crescimento de esforços no controle, desde 1986, a dengue, em Fortaleza, Nordeste do Brasil, continua endêmica com esporádicos surtos epidêmicos. Diversos fatores influenciam a ecologia do vetor, como as políticas sociais, a migração, a urbanização, o abastecimento urbano de água, a coleta de resíduos sólidos, as condições das casas, assim como as interpretações e práticas da comunidade. Este estudo descritivo utiliza uma abordagem multidisciplinar conjugando a antropologia e a entomologia. Foi adotado um desenho de estudo de caso múltiplo em seis quarteirões da cidade. O abastecimento de água é irregular seja nas casas pobres, seja naquelas privilegiadas. Apesar disso, existem diferenças entre os quarteirões em áreas pobres e aqueles mais privilegiados. Nos quarteirões mais privilegiados, existem casas que não têm ligação com o sistema de abastecimento público mas têm sistemas com poço e bomba, por isso a irregularidade não os afeta. Nos domicílios mais pobres, onde o abastecimento de água é irregular, a utilização de reservatórios como caixas d'água, cisternas, tambores, potes, cria as condições ambientais para um maior número de criadouros potenciais que poderiam incrementar a sobrevivência do Aedes aegypti.